Approximating deformation fields for the analysis of continuous heterogeneity of biological macromolecules by 3D Zernike polynomials. (2021) - Herreros, David; Lederman, Roy R.; Krieger, James; Jime´nez-Moreno, Amaya; , Marta; Mysˇka, David; Strelak, David; Filipovic, Jiri; Bahar, Ivet; Carazo, Jose Maria; Sanchez, Carlos Oscar S.
No abstract available